EFFICIENCY OF WHEAT PRODUCTION BASED ON OUTGROWER SUPPORT MODEL AMONG FARMING HOUSEHOLDS IN JIGAWA AND KANO STATE, NIGERIA - ADEKEYE , MOJISOLA DEBORAH; ABDULAZEEZ , MUHAMMAD-LAWAL; IYIOLA , OLUMIDE AYOBAMI; OWOLABI, MARVELLOUS TEMILOLUWA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the significant difference in the efficiency of wheat production among various out-growers support models in Kano and Jigawa States, Nigeria. Using primary data from 473 respondents, the study employs Stochastic Frontier Analysis (SFA) to measure technical efficiency and ANOVA to assess significant differences among the support models. The findings reveal that 81.61% of farmers participate in out-grower schemes, with the Market Input Credit-Technical Assistance (MITa) model achieving the highest efficiency (65.84%). While guarantee market access improves efficiency, land provision without complementary support is inadequate. The study concludes that a holistic support framework, integrating market access, input provision, and technical assistance, is essential for optimizing wheat production efficiency. The study recommends MITA Model for enhanced access to financial resources, technical training, extension services and guaranteed market to strengthen smallholder farmers’ capacity and efficiency of food production